170k views
5 votes
9(x + 1) = 25 + x
x = 2
x = 3
x = 4
X
11

2 Answers

5 votes

Answer:

x = 2

Explanation:

Given

9(x + 1) = 25 + x ← distribute parenthesis on left side

9x + 9 = 25 + x ( subtract x from both sides )

8x + 9 = 25 ( subtract 9 from both sides )

8x = 16 ( divide both sides by 8 )

x = 2

User TaylorOtwell
by
5.0k points
2 votes

Answer:

x = 2.

Explanation:

9(x + 1) = 25 + x

9x + 9 = 25 + x

Subtract x from both sides:

9x - x + 9 = 25

Subtract 9 from both sides:

9x - x = 25 - 9

8x = 16

x = 16/8 = 2.

User Frank Van Wijk
by
5.0k points